2017
DOI: 10.1002/ijc.31170
|View full text |Cite
|
Sign up to set email alerts
|

The arginine metabolome in acute lymphoblastic leukemia can be targeted by the pegylated‐recombinant arginase I BCT‐100

Abstract: Arginine is a semi‐essential amino acid that plays a key role in cell survival and proliferation in normal and malignant cells. BCT‐100, a pegylated (PEG) recombinant human arginase, can deplete arginine and starve malignant cells of the amino acid. Acute lymphoblastic leukemia (ALL) is the most common cancer of childhood, yet for patients with high risk or relapsed disease prognosis remains poor. We show that BCT‐100 is cytotoxic to ALL blasts from patients in vitro by necrosis, and is synergistic in combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 44 publications
(96 reference statements)
2
40
0
3
Order By: Relevance
“…Growth of melanoma cell line xenografts was significantly inhibited [ 11 ]. Among other tumour types, BCT-100 has demonstrated preclinical activity, and clinical responses have been seen in two clinical trials in adults with advanced hepatocellular carcinoma (HCC) [ 9 , 10 , 12 ]. The patient experienced no drug limiting toxicity or immunogenicity even after more than 2 years of weekly treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth of melanoma cell line xenografts was significantly inhibited [ 11 ]. Among other tumour types, BCT-100 has demonstrated preclinical activity, and clinical responses have been seen in two clinical trials in adults with advanced hepatocellular carcinoma (HCC) [ 9 , 10 , 12 ]. The patient experienced no drug limiting toxicity or immunogenicity even after more than 2 years of weekly treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Classically arginine depleting therapies such as pegylated arginine deiminase or BCT-100 are most effective when one or more of the enzymes have low or absent expression [ 8 , 13 ]. Interestingly, BCT-100 also has activity against tumours which express both ASS and OTC, unlike ADI-PEG, suggesting differences in their modes of action or other intracellular pathways are contributing to determine cell fate [ 7 , 9 , 10 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…), it is important to note the age‐associated increase in bone marrow adipocytes, which can influence oncogenesis through chemokine signaling, as well providing fatty acid substrates for FAO, a key metabolic adaptation observed in some leukemic cells and discussed earlier in this review. Additional niche metabolites can also contribute to HSC and cancer cell behavior, with studies looking at the levels of arginine and asparagine on leukemic cell response. Valine has also been recently revealed as an important effector of the bone marrow microenvironment, although more work will be required to elucidate implications for oncogenesis.…”
Section: Conclusion—tumor Microenvironmentmentioning
confidence: 99%
“…In-depth research into various aspects on tumor metabolism reveals metabolic therapy might be a promising option for cancer treatment (11). It has been demonstrated that certain cancer cells (arginine auxotrophy) cannot synthesize arginine independently and are reliant on extracellular arginine for growth (12,13). Therefore, arginine deprivation might be an Achilles' Heel for arginine auxotrophic cancers, including hepatic cell carcinoma, prostate cancer, melanoma, small cell lung cancer and leukemia (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with endogenous arginase, BCT-100 catalyzes arginine to ornithine and urea, leading to arginine depletion (19). It has been demonstrated that BCT-100 showed signi cant anticancer effects against several arginine auxotrophic cancers and completed clinical trials on HCC with promising outcomes (12,13,20). Few studies have emphasized the role of BCT-100 on bladder cancer.…”
Section: Introductionmentioning
confidence: 99%